The effects of levamisole, receiving diets, and pre and post transit potassium on fain and health of stressed calves - Brazle, F.K.; Blecha, Frank; McLaren, J.B.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We purchased 264 calves (125 bulls and 139 steers) in Tennessee and transported them to Kansas to evaluate the effects of levamisole injections and potassium supplementation, before and after transit, and feedlot receiving rations on performance and health of stressed calves. The calves were held for 48 to 96 hours in the order-buyer barn, fed either a 1.1% or 1.5% potassium (K) ration, transported for 24 hours, and fed either a 40% concentrate or hay-plus protein-supplement receiving diet fortified with either 1.1 or 1.7% K for 28 days. They were met in Kansas with 16 hr of cold driving rain, followed by severe cold temperatures, so stress was extreme. Subsequently, the calves grazed native pasture for 60 days. Levamisole reduced (P<.10) feedlot mortality. Bulls were castrated upon arrival and levamisole reduced mortality in castrated bull calves more than in steer calves (P<.05). Levamisole tended to increase IBR antibody titers and enhance change in BVD titers. Mortality was 12.3% in calves fed the 40% concentrate diet and 8.5% in those fed hay and protein supplement. More (P<.10) medical treatments per calf were required in the concentrate-fed calves than in the hay-fed calves. Due to the extreme-stress conditions during the first week in the feedlot, the calves required most of the 28-day receiving period to recover purchase weight and gains were similar (P>.05) in all groups. Fewer of the calves fed the 1.5% K pretransit diet died during the first 3 days in the feedlot than of those fed the control diet, but the posttransit K (1.7% K) diet resulted in a trend toward higher mortality during the receiving period.
Keywords: Beef; Levamisole; Diets; Potassium; Gain; Health